PANAKAWAN WAYANG KULIT PURWA: Asal-usul dan Konsep Perwujudannya - Sunarto - (PANGGUNG, 2012)
Panakawan is a group of purwa shadow puppet having a specific embodiment. The embodiment of panakawan figures is shown in unproportional body and caricaturistics. The question is since when panakawan figures appear and how the concept of embodiment is. To answer that question, the research is done through historical approach to track the existence of panakawan figures, while the iconography is used to identify panakawan figures in terms of embodiment, and in tracing the concept of panakawan embodiment is done through structural approach.This study found that panakawan history can be traced through two sources, namely verbal and pictorial sources. Verbal is any source that is obtained from written works, whereas pictorial is any source of artifacts. The term of Panakawan was first found on serat Gattkacasraya by Empu Panuluh in the eleventh century and on Kitab Nawaruci by Empu Siwamurti in the fifteenth century. Panakawan was also found on several sources of puppet plays, among others: Kidung Sudamala, Serat Purwakanda, Serat Pustakarajapurwa, and Serat Purwacarita. On artifact sources, it was found on temple reliefs and on some kinds of puppet. The concept of panakawan embodiment was inspired by the disabled people who have magic power. The people of this type in Yogyakarta palace are called Abdi Dalem Palawija, whereas in the ancient Java they were included in the character of i’jro. Keywords: Panakawan, history, concept